Investigating the perception and acceptance towards smartphone and its application as learning tool among Universiti Teknologi MARA dental students / Nor Faharina Abdul Hamid, Nur Saiyidah Hanisah Ali and Nadia Syahirah Mohd Nazri. - Abdul Hamid, Nor Faharina; Ali, Nur Saiyidah Hanisah; Mohd Nazri, Nadia Syahirah (2019)
The development of smartphones throughout the years had made it a very valuable tool in teaching and learning activities. The purpose of this study was to investigate the perception and acceptance towards the use of smartphones as additional learning tool among Universiti Teknologi MARA (UiTM) dental students. Methods: All undergraduate dental students were invited to participate in a self‐ administered questionnaire (content validated, pre-tested) survey, conducted online, involving students across all academic years. Results: Of the 215 respondents, (99.1%) owned a smartphone, with majority of them were iPhone and Android user. 94%, n=202 of the respondent had access to internet data via a third generation (3G) mobile carrier and WiFi connection. Most of the respondents gave positive remarks of all ten statements in regards the perception and acceptance towards smartphone and its application as learning tool. 96.7%, n=208 of respondents agreed that smart phone help them in finding resources related to their study while 74%, n= 159 of them stated that smartphone can help them to manage their study. Conclusion: In conclusion, the results of this study suggested that UiTM undergraduate dental students have positive perception and acceptance towards use smartphones in teaching and learning activities.